Criminalistic context of concepts of deception and lie in the activities of law enforcement bodies: the problem of denial - Krasikau, Uladzimir S. (Journal of the Belarusian State University. Law, 2022)
The problem of denial of deception and lies in the context of forensic science and operational-search activity is investigated. The current points of view on the problem of inadmissibility of deception and lies have been studied, possible criteria for assessing the admissibility of methods of carrying out investigative actions and carrying out operational-search measures have been determined, directions for researching the problems of forensic (investigative, operational search) tactics used by authorised state bodies in the framework of an investigation, detection and prevention of criminal activity have been determined.
Keywords: forensic context of deception and lies; forensic, investigative, operational-search tactics; the intellectual aspect of deception and lies